Tourists’ Intentions Towards Eco-friendly Destinations and Their Significance in Sustainable Tourism Development - Bhim Bahadur Khadka; Anjani Kumar Malviya (Journal of Nepalese Management and Research, 2024)
The study aims to investigate the influence of the personal values of tourists on their attitudes, subjective norms and perceived behavioural control. Furthermore, the study aims to evaluate the subsequent impact of these factors on tourists' intentions to visit eco-friendly destinations. Additionally, the study examines the moderating role of environmental consciousness in shaping the relationship between personal values and attitudes towards sustainable tourism practices. The study uses convenience sampling to gather data from tourists at two distinct eco-friendly tourist sites, Bulbule and Kankrebihar, located in the Surkhet district of Nepal. The study involves accessing the reliability and validity of the measurement model, followed by path analysis of the structural equation modelling, followed by path analysis of the structural model. The study conducts confirmatory factor analysis to validate the latent constructs. Survey data from 405 tourists reveal significant positive relationships between tourists' values of resultant self-transcendence and conservation and TPB factors, except for the relationship between conservation and perceived behavioural control. Moreover, TPB factors and perceived green image positively influence tourists' intentions to visit eco-friendly destinations. Likewise, environmental consciousness moderates the relationships between the two Schwartz values and attitudes. In addition, the study offers valuable implications for sustainable tourism operators and eco-friendly destination managers, highlighting the need to consider individual values and environmental consciousness in promoting eco-friendly behaviours.